Using a Nitrophenol Cocktail Screen to Improve Catalyst Down‐selection. Issue 15 (8th July 2020) - Shultz, Lorianne R.; Hu, Lin; Feng, Xiaofeng; Jurca, Titel
Abstract: The catalytic reduction of 4‐nitrophenol (4NP ) with excess NaBH4 is the benchmark model for quantifying catalytic activity of nanoparticles. Although broadly useful, the reaction can be very selective. This can lead to false positives and negatives when utilized for catalyst down‐selection from a broader materials candidate pool. We report a multi‐nitrophenol cocktail screening methodology incorporating 4NP and other amino‐nitrophenols, utilizing Ag, Au, Pt, and Pd nanoparticles on carbon support. The reduction of the cocktail proceeds with no deleterious side reactions on the time‐scale tested. The resulting kinetic rates provide an improved correlation of relative catalyst activity when compared to performance with other reducible moieties (e. g. azo bonds), or when compared to solely 4NP screening. Abstract : The catalytic reduction of 4‐nitrophenol is the benchmark model for testing the catalytic activity of nanoparticles. A single‐molecule probe is however prone to disparate selectivity, leading to false rankings for catalyst down‐selection. The authors report a facile multi‐nitrophenol cocktail screening method. When tested with noble‐metal nanoparticles, the cocktail approach provides an improved ranking of the relative catalyst activity when compared to the reduction of azo bonds.